Use of ChatGPT in Low-Code Development: An Exploratory Study in the Salesforce Platform - Falcão Filho, Odimar; Buarque, Brenno; Almendra, Camilo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248603, 2026)
Research Context: Large Language Models (LLMs) have emerged as promising resources to support software development. Beyond code generation, these tools can serve as technical and educational support, assisting developers in learning and applying concepts in complex low-code development platforms (LCDP). Scientific and/or Practical Problem: While LCDPs lower entry barriers, organizations still struggle to adopt them. As a first step, we investigate whether LLMs can effectively assist LCDP’s newcomers in learning, producing and deploying quality enterprise applications. Proposed Solution and/or Analysis: This paper presents an exploratory study on the use of ChatGPT to support the development of a Salesforce application. We focus on a zero-shot learning approach to resemble the profile of newcomers. The study aims to identify the suitability of LLMs to assist beginner low-code developer. Related IS Theory: ChatGPT is seen as part of a socio-technical network that transforms low-code development. Information systems are complex and require interoperability; in this context, generative AI expands accessibility and innovation. Research Method: Development of a low-code application through prompts, using ChatGPT as support. Evaluation of the application based on quantitative and qualitative metrics. Summary of Results: Simple requirements were often solved with a single prompt, whereas the most complex required iterations and significant debugging, revealing the model’s limits. Expert reviewers found the AI-generated solutions correct and aligned with Salesforce best practices, but noted that the code lacked structural best practices. Contributions and Impact to IS area: Contributes to SI by demonstrating that ChatGPT is a co-creative, educational partner that can boost development productivity and democratize development by lowering technical barriers. However, human expertise remains critical. This work demonstrates how strategic AI integration can enhance system delivery while supporting developer learning.